Environmentally Friendly Larvicides: A Post-Test Only Experimental Comparison of Eleutherine palmifolia and Allium sativum Extracts (0.6–1.8%) on Aedes aegypti Larval Mortality - Nuryanto, Muhammad Khairul; Nurkhalisa, Nina; Rasendriya , Fauzan Firjatullah; Saputra, Rudi; Fitriany, Evi; Duma, Krispinus; Tandirogang, Nataniel (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aims to identify the larvicidal potential of Eleutherine palmifolia (Dayak onion) and Allium sativum (garlic), which are rich in flavonoids and known to possess insecticidal properties. The study used a pure experimental design with a post-test control group. Aedes aegypti larvae were tested with Eleutherine palmifolia and Allium sativum extracts at concentrations of 0.6%, 1.2%, and 1.8%, respectively, along with abate as a positive control. Larval mortality was monitored for 24 hours with four replicates. The results showed that Allium sativum was highly effective at all concentrations (99–100% mortality), even at the 0.6% concentration. In contrast, Eleutherine palmifolia exhibited varying effectiveness, with mortality rates of 67%, 67%, and 84% at concentrations of 0.6%, 1.2%, and 1.8%, respectively. These findings confirm that Allium sativum has superior, consistent, and stable larvicidal effectiveness even at low doses, making it a promising alternative for mosquito control and dengue prevention.